Legal Analysis of Online Gambling with the Higgs Domino Island Online Game Mode According to The Perspective Criminal Law in Indonesia - Ahmad Novaisal; Sumarno Sumarno; Firman Halawa (CV. Era Digital Nusantara, 2025)
This study discusses the legal analysis of online gambling practices using the Higgs Domino Islands game from the perspective of criminal law in Indonesia. The purpose of the study is to assess the extent to which applicable laws and regulations are able to ensnare gambling activities camouflaged through digital game media. The research method uses a normative juridical approach by examining the provisions of the Criminal Code, Law Number 7 of 1974 concerning the Regulation of Gambling, and Law Number 11 of 2008 concerning Electronic Information and Transactions. The results of the study indicate that the Higgs Domino Islands game has characteristics that fulfill the elements of gambling because it involves betting, opportunities, and real economic benefits. However, law enforcement is still not optimal due to limited regulations that do not explicitly regulate the form of digital gambling and technical obstacles in proving electronic transactions. Legal updates and increased capacity of law enforcement officers are needed to be able to keep up with the development of digital technology. This research is expected to contribute to strengthening criminal law policies in facing the challenges of online gambling in the digital era.